2014
DOI: 10.17718/tojde.52135
|View full text |Cite
|
Sign up to set email alerts
|

ICT Usage By Distance Learners In India

Abstract: Open Universities across the world are embracing ICT based teaching and learning process to disseminate quality education to their learners spread across the globe. In India availability and access of ICT and learner characteristics are uneven and vary from state to state. Hence it is important to establish the facts about ICT access among learners, their ICT usage patterns and their readiness to use ICT for educational purpose. In view of this, a study was conducted with the objective to find out the access l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Awadhiya, Miglani and Gowthaman (2014) acknowledge the use of ICTs in open universities worldwide. In India, though use of ICTs is not evenly distributed, in Awadhiya's et al (2014) study, they found that most distance learners in India access the Internet through laptops, desktops and smartphones. Through use of ICTs, higher education is promoted and transformed, "from a teacher directed enterprise towards student-centered models" (Kaur & Nanak, 2015, para.…”
Section: Review Of Literaturementioning
confidence: 92%
“…Awadhiya, Miglani and Gowthaman (2014) acknowledge the use of ICTs in open universities worldwide. In India, though use of ICTs is not evenly distributed, in Awadhiya's et al (2014) study, they found that most distance learners in India access the Internet through laptops, desktops and smartphones. Through use of ICTs, higher education is promoted and transformed, "from a teacher directed enterprise towards student-centered models" (Kaur & Nanak, 2015, para.…”
Section: Review Of Literaturementioning
confidence: 92%
“…In this context, the studies available in the relevant literature show that not only are social media networks widely used in open and distance learning environments, they also yield positive results (Awadhiya et al, 2014;Blaschke, 2014;Seaman & Tinti-Kane, 2013;Thoms & Eryilmaz, 2014).…”
Section: Problemmentioning
confidence: 99%
“…The literature includes certain studies on the use of social media to increase interaction between learners and instructors in open and distance learning environments (Van Wyk, 2014). A study conducted in IGNOU, an open university in India, identified the objectives of internet use and revealed that open and distance learners mostly used (80%) such social media as Facebook, Twitter, YouTube, and Blogs for learning and teaching purposes (Awadhiya, Miglani, & Gowthaman, 2014). In another study revealing the importance of social media use in open and distance learning environments, Özmen and Atıcı (2014b) not only concluded that learners using social media in open and distance learning environments develop positive attitudes toward lessons but also reported increased quality of communication between "learner -learner" and "instructor -learner."…”
mentioning
confidence: 99%
“…The ODL Institutions across the world are embracing ICT based teaching-learning process to disseminate quality education to their learners spread across the globe. In India, availability and access to ICT facilities and learner characteristics are uneven and vary from state to state (Awadhiya, Miglani & Gowthaman, 2014). In ODL and other Institutions of learning, designing, developing, and introducing learner support services with a learner-centric philosophy is a fundamental element in ensuring that they fulfill their intended purpose (Hunte, 2012).…”
Section: Introductionmentioning
confidence: 99%